PENGARUH RANSUM DENGAN KADAR SERAT KASAR BERBEDA TERHADAP ORGAN DALAM AYAM JANTAN TIPE MEDIUM UMUR 8 MINGGUPENGARUH RANSUM DENGAN KADAR SERAT KASAR BERBEDA TERHADAP ORGAN DALAM AYAM JANTAN TIPE MEDIUM UMUR 8 MINGGU - Gusma Gama Maradona; Rudy Sutrisna; Erwanto . (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2015)
Type of medium rooster has been used as a livestock producer of meat. This study aims to: 1) determine the effect of different levels crude fiber in ration to weight liver, gizzard and intestine rooster type of medium age of 8 weeks; 2) determine the best crude fiber level in ration on weight liver, gizzard and intestine rooster type of medium age of 8 weeks. This study was conducted in 12 September until 20 October 2014 located in the cage of Ramajaya in Karang Anyar Farm, Fajar Baru, Jati Agung, South of Lampung. The analysis of feed was conducted in Laboratory of Animal Feed, Departement of Animal Husbandry, Faculty of Agriculture, University of Lampung. This study used completely randomized design (CRD) with 4 treatments and 3 replications. R0 = ration with crude fiber content of 4%, R1 = ration with crude fiber content of 6%, R2 = ration with crude fiber content of 8% and R3 = ration containing 10% crude fiber. Data obtained was statistically tested to determine the effect of treatments to the variables observed by variance analysis. Then, it was continued by using Least Significant Different (LSD) on significant level 5%. The result of this study showed that ration with different levels of crude fiber (R0 = 4%, 6% R1 = R2 = R3 = 8% and 10%) was not significant (P> 0.05) to the internal organs rooster type of medium age of 8 weeks